the Way It Is / The Construction of Organizational Culture - Leontiou, Janet Farrell ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1970)
An ethnographic study examined the sense of the social world as a natural order produced by the organizational members of one sales team at a New York media representation firm. Communication was observed and recorded over a ten-week period, and members of the sales team were interviewed during an additional two-week period. Results indicated that sexism had achieved the status of fact within the organization's culture. Considerable observation of the organizational culture of the subject sales team showed that there is not one culture but two--the corporate culture and the female subculture of the sales assistants. The complementary nature of the female subculture and the corporate culture is a key to how the sense of the natural order is preserved by the organizational members, providing them with a sense of continuity, balance, and completeness, while, at the same time, furnishing the sales assistants with a domain and a set of activities of their own. Findings suggest that the preservation and maintenance of the existing order of the subject sales team is a social accomplishment produced by both the corporate culture and the female subculture. (Extensive footnotes and a bibliography are appended.) (NKA)
ERIC Note: Paper presented at the Annual Meeting of the Eastern Communication Association (78th, Syracuse, NY, May 18-21, 1987).
Microfiche.
Keywords: Communication Research; Cultural Context; Employee Attitudes; Employer Employee Relationship; Ethnography; Females; Job Satisfaction; Organizational Climate; Organizational Communication; Sex Bias; Social Structure; Vertical Organization; Work Environment; Hierarchical Control -- Organizational Culture; Organizational Research; Reference Materials, Vocabularies/Classifications.; Speeches/Meeting Papers